PENINGKATAN HASIL BELAJAR TEMATIK MENGGUNAKAN MODEL COOPERATIVE SCRIPT KELAS IV SD - Tri Wiyoko; Subhanadri Subhanadri; Ayu Afelia Indah (Jurnal Pendidikan, 2021)
The problem in this research is that the learning outcomes of students in grade IV SD 04 / II Jaya Setia are still low, this is evidenced by the results of preliminary observations made by researchers from 34 students, only 29% who scored in the complete criteria. The reason is that students in the class are passive, have not used varied learning models, and have not used concrete in learning. The research objective is to improve the process and thematic learning outcomes through the application of cooperative learning model cooperative scripts. The research model used in this research is classroom action research. Data collection using observation sheets for the learning process of students and tests for student learning outcomes. The results showed an increase in thematic learning outcomes in class IV SDN 04 / II Jaya Setia after using the cooperative script model. The results obtained indicate that the increase in the quality of the learning process from cycle I to cycle II reaches the very good category. Furthermore, the learning outcomes obtained in cycle I were 53% of students who completed and increased in cycle II by 82% of students who completed. So the cooperative script model can improve the thematic learning outcomes of class IV students.